The Formation of Ethnically Distinct Villages in Jember during the Colonial Period (1870-1942) - Widuatie, Ratna Endang; Winarni, Retno (Indonesian Historical Studies, 2024)
The development of the plantation economy in Jember at the end of the 19th century required a large workforce, something that could not be met by the local population. The colonial government responded by bringing in workers from western East Java, the Vorstenlanden, and Madura Island. These migrants eventually settled in Jember and became pioneers for subsequent waves of migration until the Second World War. The entry of Javanese and Madurese people into Jember shaped the physical characteristics of settlements that have survived to this day. The settlement arrangements made by the colonial government were based on ecological and cultural considerations of migrants, and plantation-oriented resulted in a unique pattern of segregation. After Indonesia's independence, villages in Jember became more fluid in terms of demographic composition, however, the physical and cultural characteristics that indicate a village has Javanese or Madurese cultural roots are still clearly visible. This article describes the process of the formation of villages in Jember with a comparison of “Javanese villages” and “Madurese villages” to find out how far the colonial government's intervention influenced the formation of villages, and how the villagers concerned maintain their cultural identity as migrant newcomers.